1993
DOI: 10.1007/bf02189308
|View full text |Cite
|
Sign up to set email alerts
|

On sparse spanners of weighted graphs

Abstract: In this paper we give a simple algorithm for constructing sparse spanners for arbitrary weighted graphs. We then apply this algorithm to obtain specific results for planar graphs and Euclidean graphs. We discuss the optimality of our results and present several nearly matching lower bounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
481
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 481 publications
(487 citation statements)
references
References 18 publications
5
481
0
1
Order By: Relevance
“…It was shown [1,2] that these techniques produce t-spanners with n 1+O( 1 t−1 ) edges on general graphs of n nodes.…”
Section: T-spanner Construction Algorithmsmentioning
confidence: 99%
“…It was shown [1,2] that these techniques produce t-spanners with n 1+O( 1 t−1 ) edges on general graphs of n nodes.…”
Section: T-spanner Construction Algorithmsmentioning
confidence: 99%
“…A lower bound on the number of edges is n -1 because a spanning tree is a connected graph with the fewest edges. Spanners with O(n) edges and constant stretch factors have been designed in several papers, but in most of these spanners the c~nstant implicit in the O-notation depends on the dimension [1,2,3,4,7,9,10,14]. The degree-4 spanner constructed in [11] is an improvement, because it has at most 2. n edges.…”
Section: B For K < 3 Its Weight Is O(1) Wt(mst) and For K > 3 Its mentioning
confidence: 99%
“…This has been answered in the affirmative in 2-dimensions. In [1] it is shown that, given any 5 > 1, a spanner with a constant stretch factor (which depends on 5) can be constructed with at most n. 5 edges. However, the techniques employ planarity properties and do not extend to higher dimensions.…”
Section: B For K < 3 Its Weight Is O(1) Wt(mst) and For K > 3 Its mentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable work has been done on the spanner of a graph. In general, a t-spanner of G is a low-weight subgraph of G such that, for any two vertices, the distance within the spanner is at most t times the distance in G. Some results of finding spanners of a weighted graph can be found in [1]. Obviously, the spanners can be used to approximate the minimum routing cost subgraph with arbitrary requirements.…”
Section: Introductionmentioning
confidence: 99%